2022
DOI: 10.1111/jcpe.13694
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linked hyaluronic acid gel with or without a collagen matrix in the treatment of class III furcation defects: A histologic and histomorphometric study in dogs

Abstract: Aim: To histologically evaluate the effects of cross-linked hyaluronic acid (xHyA) with or without a collagen matrix (CM) on periodontal wound healing/regeneration in class III furcation defects in dogs. Materials and Methods: Class III furcation defects were surgically created in the mandibular premolars in six beagle dogs. The defects were randomly treated as follows: open flap debridement (OFD) + CM (CM), OFD + xHyA (xHyA), OFD +-xHyA + CM (xHyA/CM) and OFD alone (OFD). At 10 weeks, the animals were euthani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
5
18
0
Order By: Relevance
“…The histomorphometric assessments revealed that xHyA-treated intraosseous and furcation sites formed significantly greater areas of new cementum and periodontal ligament fibers on previously exposed root surfaces. Similar observations were made from the same treatment sequence applied in gingival recessions [ 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 72%
“…The histomorphometric assessments revealed that xHyA-treated intraosseous and furcation sites formed significantly greater areas of new cementum and periodontal ligament fibers on previously exposed root surfaces. Similar observations were made from the same treatment sequence applied in gingival recessions [ 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 72%
“…28,29 The periodontal wound healing/regeneration effects were further supported by in vitro studies showing that HA: (a) acts as lubricant and space filler 30 ; (b) preserves human periodontal ligament cell viability and increased early osteogenic differentiation 31 ; (c) controls the balance between selfrenewal and differentiation during bone regeneration 32 ; and (d) induces root cementum, periodontal ligament, and bone formation in experimentally created two-wall intrabony defects in dogs. 33 Based on the above-mentioned properties, HA effects on nonsurgical periodontal treatment were also investigated. In particular, it was applied in (a) initial periodontal treatment as a monotherapy or associated with subgingival instrumentation, showing moderate improvement of clinical parameters; 34,35 and (b) as an adjunctive therapy in conjunction to subgingival re-instrumentation of residual pockets, resulting in nonstatistically significant differences compared with nonsurgical retreatment alone.…”
Section: Introductionmentioning
confidence: 99%
“…Shirakata et al conducted an experimental study on dogs in which they found successful periodontal regeneration of gingival recession defects after treatment with CAF + HA. Statistically significant differences were observed in CAL (p < 0.05), width of gingival recession (p < 0.01), in formation of cementum and connective tissue attachment (p < 0.05) at 10 weeks in HA + CAF group [43]. From these observations we can assume some amount of true regeneration to take place under CAF with connective tissue attachment [41].…”
Section: Discussionmentioning
confidence: 99%